A Political-Economic Analysis of Free-Trade Agreements - Levy, Philip I. (American Economic Review, 1997)
This paper demonstrates that bilateral free-trade agreements can undermine political support for further multilateral trade liberalization. If a bilateral trade agreement offers disproportionately large gains to key agents in a country, then their reservation utility is raised above the multilateral free-trade level, and a multilateral agreement would be blocked. Bilateral agreements between countries with similar factor endowments are most likely to have this effect. It also follows that bilateral free-trade agreements can never increase political support for multilateral free trade.